The impact of cognitive restructuring in group counseling on students' self-efficacy in writing theses - ramadhany, kharisma aulia; farid, dimas ardika miftah (Universitas Islam Negeri Raden Intan Lampung, 2025)
The purpose of this study was to determine the impact of group counseling with cognitive restructuring techniques on students' self-efficacy in writing a thesis. This study used a quantitative approach with a pre-test and post-test design in one group, and involved six students of the Faculty of Education, Universitas PGRI Adi Buana Surabaya, Faculty of Education, Class of 2021. The results of the study showed a significant increase in students' self-efficacy after group counseling with cognitive restructuring techniques; the Wilcoxon test showed a significant change, with Asymp. Sig. Value. (2-tail) of 0.027 (<0.05). Because cognitive restructuring techniques have been proven to be successful in helping students improve their thesis writing, it can be concluded that group counseling with cognitive restructuring techniques has an impact on students' self-efficacy in writing a thesis